2014
DOI: 10.1155/2014/243539
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Optimally Timed Osteopathic Manipulative Treatment on Length of Hospital Stay in Moderate and Late Preterm Infants: Results from a RCT

Abstract: Introduction. Little research has been conducted looking at the effects of osteopathic manipulative treatment (OMT) on preterm infants. Aim of the Study. This study hypothesized that osteopathic care is effective in reducing length of hospital stay and that early OMT produces the most pronounced benefit, compared to moderately early and late OMT. A secondary outcome was to estimate hospital cost savings by the use of OMT. Methods. 110 newborns ranging from 32- to 37-week gestation were randomized to receive ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
5
27
0
2
Order By: Relevance
“…[27] Four out of 5 trials were single-center [2729,31] and 1 multicenter. [30] Newborns population ranged from severe to late prematurity (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Four out of 5 trials were single-center [2729,31] and 1 multicenter. [30] Newborns population ranged from severe to late prematurity (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, treatment was performed either by osteopaths [2730] or by student in osteopathy, [31] but only 2 studies [28,29] gave data on the number of practitioners enrolled, 4 and 2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…15 titles were selected for full text review and 5 were omitted because they were not full text manuscripts (two were poster presentations, one was an oral presentation, one was a protocol for an already published RCT included in this paper) or they were not performed as an osteopathic technique (one had physiotherapist perform manipulation). Of the 10 remaining titles, there was one case study, one prospective observational study, one Three different RCTs, Cerritelli and associates [13], Pizzolorusso and associates [14], and Cerritelli and associates [15] examined the effect of OMT on LOS in preterm infants at different time periods.…”
Section: Resultsmentioning
confidence: 99%
“…The present systematic review found a variety of studies and the aim of this paper was to summarize the evidence of using osteopathic medicine as diagnosis and to evaluate the effectiveness of OMT as an adjunct treatment option for infants in the NICU. Ten articles were found addressing the use of OMT in the NICU, six studies favored OMT and showed a positive effect [10,[12][13][14][15][16], one showed a negative effect [17], two did not report any between group comparisons [11,18], and the remaining one describes a study protocol and the study results have not yet been published [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation